Opini Digital #PERMEDIKBUD30 pada Media Sosial Tiwitter - Rafli Ramadhan; Rian Andika; Wa Ode Sapnano Filanti (Journal of Government Insight, 2021)
This paper aims to determine the perception or opinion formed in the community on the hashtag #permendikbud30 on social media twitter. The research method used is mixed methods by combining quantitative methods for statistical calculation of communication networks with a sample of 67 tweet data, 5 actors and 62 relations using netlytic and gephi, with a qualitative method for analyzing text using Digital Movement of Opinion which describes and explains the network. social network and structure. The results of this study show that #permendikbud30 is able to create the ability of netizens' opinions in a communication network with the help of the role of @sumntra_14 popular actor. Another finding is that the Minister of Education and Culture No. 30 of 2021 has support. Warganet gives a new hashtag #supportPermendikbud30.